العبادات الهندوسية في بنجلاديش دراسة نقدية: Hindu worships in Bangladesh, a critical study - Rafiqul Islam , Habibur Rahman; Md. Zain, Aman Daima (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2022)
ملخص إن العبادات المنتشرة في الديانة الهندوسية وغيرها من الديانات ليس لها أية قيمة عند الله تبارك وتعالى وليس لهم جزاء في الآخرة بهذه العبادات المرفوضة، إن كثيرًا من المسلمين في بنجلادش يعتقدون أن العبادات غير متواجدة في الديانة الهندوسية إلا في الإسلام، فيشاركون الهندوسية أعيادهم واحتفالاتهم بجهالة، وتأثر المسلمون في بنجلاديش بالديانة الهندوسية فتأثرت عباداتهم بعباداتهم. وهنا تكمن مشكلة البحث. ويهدف البحث: إلى أن في الهندوسية عبادات خاصة كما في الإسلام ولكنها مختلفة بطرقها، وأن عباداتهم خاصة للآلهة وليست لله الواحد الأحد، وكذلك التعرف على كيفية العبادات في الديانة الهندوسية وموقف الإسلام منها. وقد اتخذ البحث المنهج الكيفي: اعتماداً على الاستقراء ومعرفة مفهوم الأديان الوضعية، والمنهج التحليلي لبيان حقيقة عبادات الديانة الهندوسية، ومدى تأثيرها على مسلمي بنجلاديش ووجودها داخل بنجلادش. وقد نتج عن البحث: أن الهندوسية ديانةٌ وثنية من الديانات المعاصرة التي يدين بها عدد كبير من الناس. وأن رأس الآلهة الهندوسية في بنجلادش التي يعبدونها هي الأصنام. وأن عبادات الهندوسية ثمرات لتجارب الأمم التي أدت دورها في تكوين الفكر الهندوسي. Abstract Many kinds of worships that spread in Hinduism and other religions have no value to Allah, the Blessed and Exalted, and there will be no reward in the Hereafter for whosoever engage with these rejected worships. Many Muslims in Bangladesh believe that worship does not exist in the Hindu religion except in Islam, so they participate in Hinduism in their feasts and celebrations in ignorance. The Muslims in Bangladesh were influenced by the Hindu religion, so their worship was affected by their worship. Herein lies the research problem. The research aims: that in Hinduism there are special worships as in Islam, but they are different in their ways, and that their worship is specific to the gods and not to The One and Only God, as well as to identify the way of worship in the Hindu religion and the position of Islam towards it. The research took the qualitative approach: based on induction and knowledge of the concept of man-made religions, and the analytical approach to clarify the reality of Hindu religious worship, and the extent of its impact on the Muslims of Bangladesh and its presence in Bangladesh. The result of the research: Hinduism is a pagan religion of the contemporary religions that a large number of people adhere to. And that the head of the Hindu deities in Bangladesh that they worship are idols. And that the worship of Hinduism is the fruits of the experiences of nations that played their role in the formation of Hindu thought.